Konsep Uang Dalam Islam - Choirunnisak Choirunnisak; Choiriyah Choiriyah; Sapridah Sapridah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract.This research discusses how the concept of money in Islam. This research is a type of library research that focuses on qualitative data management with data analysis methods using the description-analysis method. The results of this study stated that money is capital money, money is not identical with capital, money is public goods, capital is private goods, money is flow concept, capital is stock concept. Money is not a commodity, even money in the Islamic concept is not included in the utility function. In Islam there is no time value of money. Islam only knows the Economic Value of Time and money is a flow concept.Keywords: Concept, Money, Islam Abstrak.Penelitian ini membahas bagaimana konsep uang dalam Islam. Penelitian ini merupakan jenis penelitian pustaka (library research) yang menitikberatkan pada pengelolaan data secara kualitatif dengan metode analisis data menggunakan metode deskripsi-analisis. Hasil penelitian ini menyatakan bahwa Uang adalah uang capital, uang tidak identik dengan modal, uang adalah public goods, modal adalah private goods, uang adalah flow concept, modal adalah stock concept. Uang bukan suatu komoditi, bahkan uang dalam konsep Islam tidak termasuk dalam fungsi utility. Dalam Islam tidak mengenal adanya time value of money. Islam hanya mengenal Economic Value of Time dan uang adalah flow concept.Kata Kunci; Konsep, Uang, Islam